KEBIJAKAN BANTUAN LANGSUNG TUNAI (BLT) DALAM MEMBANTU KESEJAHTERAAN MASYARAKAT - Auliya Shalha Nasution; Mahirah Marwa Syaharani; Revi Prastanti; Yara Az-Zahra Hasibuan (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Cash (BLT) is a significant policy instrument in efforts to reduce poverty and improve community welfare. This article’s research method uses the literature study method, namely the process of collecting data from written sources, such as books and journals, to understand theories relevant to the research topic. The aim of the research is to evaluate the impact of BLT on recipient communities and examine the key aspects that influence its effectiveness. Apart from that, this article also discusses the meaning of direct cash assistance, several criteria for those who can receive BLT, the objectives of providing BLT, the advantages and disadvantages of BLT , and also the background to the implementation of BLT (Direct Cash Assistance).